Politics, Order and History : Essays on the Work of Eric Voegelin. - Hughes, Glenn (Bloomsbury Publishing, 2001)
This volume brings together critical review papers, many specially commissioned, on key themes and questions in the work of the political scientist, philosopher and religious thinker Eric Voegelin (1901-1985). Areas covered include: (1) Political science: ''Political Religions'': manifestations in Nazi Germany and in contemporary European and North American nationalism; (2) International relations: the ''Cold War'' in critical perspective; (3) Philosophy: Plato and Aristotle in the reading of Eric Voegelin: contemporary assessments; (4) Sociology: Correspondence of Voegelin and Alfred Schütz.